2014
DOI: 10.1007/s00404-014-3446-7
|View full text |Cite
|
Sign up to set email alerts
|

Success rate and safety of tumor debulking with diaphragmatic surgery for advanced epithelial ovarian cancer and peritoneal cancer

Abstract: Tumor debulking surgery with DS resulted in controllable blood loss, and OS was successful in all patients without severe complications or postoperative treatment delay. Currently, OS is considered to have very few benefits over CS; thus, the success rate of CS rate should be improved while maintaining safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The ultimate goal of cytoreductive surgery is removal of the entire tumor burden to achieve either complete removal of the tumor upon visual inspection (complete cytoreductive surgery, CCS) or a residual tumor of < 1 cm (optimal cytoreductive surgery, OCS). Only these two surgical outcomes will improve survival [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of cytoreductive surgery is removal of the entire tumor burden to achieve either complete removal of the tumor upon visual inspection (complete cytoreductive surgery, CCS) or a residual tumor of < 1 cm (optimal cytoreductive surgery, OCS). Only these two surgical outcomes will improve survival [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal debulking surgery is defined by a resulting residual tumors <1 cm at the largest diameter (4). Some studies have reported that complete and optimal debulking surgery can improve survival outcomes (5,6). Lymphatic spread is commonly observed in both early and advanced ovarian cancer (7), and retroperitoneal lymph node metastasis has been reported to be related to a poor prognosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have noted that gynecologic oncologists are expanding the surgical armamentarium for EOC, diversifying their skill sets and participating in a multidisciplinary team approach to treatment [46]. Several studies have also reported significant increases in survival, as well as a minimal but acceptable increase in morbidity, as a result of this shift in the surgical paradigm [710]. …”
Section: Introductionmentioning
confidence: 99%